2022
DOI: 10.17211/tcd.1151639
|View full text |Cite
|
Sign up to set email alerts
|

Tunceli iklim parametrelerine ait zaman serilerinin farklı istatistiksel analiz yöntemleriyle değerlendirilmesi

Abstract: One of the most challenging environmental problems facing the world society today is climate change. The negative effects of climate change on human and natural systems are increasing. To understand the effects of climate change, trends in climate data need to be studied extensively. However, the contribution of climate observations made on a global scale to planning made at local and regional scales is low. Therefore, local climate analyzes are required to evaluate and develop strategies to minimize the harmf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…In a study based on the climate parameters of Tunceli, it was found that there was a significant increase in mean temperature at a significance level of 0.05 during the period from 1965 to 2020. This increase was observed in the months of February, March, June, and August, as well as annually (Esen, 2022). In a study conducted for the province of Kilis, monthly average temperatures were examined and it was found that there was an increasing trend in the data of April, June, July, August according to the MK trend test at the 95% confidence interval (Ercan and Yüce, 2018).…”
Section: Trend Analysis Of Surface Temperaturementioning
confidence: 99%
“…In a study based on the climate parameters of Tunceli, it was found that there was a significant increase in mean temperature at a significance level of 0.05 during the period from 1965 to 2020. This increase was observed in the months of February, March, June, and August, as well as annually (Esen, 2022). In a study conducted for the province of Kilis, monthly average temperatures were examined and it was found that there was an increasing trend in the data of April, June, July, August according to the MK trend test at the 95% confidence interval (Ercan and Yüce, 2018).…”
Section: Trend Analysis Of Surface Temperaturementioning
confidence: 99%
“…The data may not accurately re ect conditions at a given location. Therefore, temperatures will often be higher than shown, especially in urban areas, and precipitation may vary locally depending on topography (Manoli et (Esen, 2022). The lower part of the graph shows warming stripes.…”
Section: Precipitation and Temperature Anomaliesmentioning
confidence: 99%
“…Ayrıca çalışmadan bölge ikliminin hayvancılık ve tarıma elverişli olduğunu ifade etmiştir. Esen (2022) tarafından iklim verilerinin uzun yıllar ortalamalarının incelenmesine yönelik olarak Tunceli ili için yapılan başka bir çalışmada ise, ilin sisli gün sayısında ve ortalama sıcaklık değerlerinde artış, bağıl nem, ortalama rüzgâr hızı, toplam yağış, yağışlı ve kar yağışlı gün sayılarında azalma yönünde eğilimler olduğu belirlenmiştir. Bölgenin ilerleyen dönemlerde olası su yetersizliği ve dolayısıyla kuraklık problemleriyle karşılaşacağı belirtilmiştir.…”
Section: Introductionunclassified